Contribution of Sit-Up Exercises on Candle Attitude Ability in Gesaid Gymnastics Club - Falinda Isnabella Wahyu Sasani; Agus Darmawan (Universitas Negeri Semarang, 2026)
Floor gymnastics is a sport that requires very complex coordination of movements, high precision, and perfect mastery of technique by combining muscle strength, flexibility, and motor coordination. In this study, it was determined to determine the contribution of sit-up exercises to candle attitudes in gymnastics gesaid club athletes. This study uses a correlational approach with one data collection. The population and sample in this study used 10 athletes with a total sampling technique. The data analysis in this study used a correlation test and a determination coefficient test. The results of the study showed that the contribution of sit-ups to the attitude of candles in gymnastics gesaid club athletes with an R square value of 0.448. It shows that the higher the strength of the abdominal muscles with the sit up exercise, the more stable it is to perform the skill by contributing 44.8% to the candle attitude of the athletes of the Gesaid Gymnastics Club. In conclusion, sit-up training is a supporting variable that directly affects the mastery of technique, position endurance, and the beauty of candlestick movements for athletes.